1988
DOI: 10.1037/0022-0167.35.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Preventing substance abuse among American-Indian adolescents: A bicultural competence skills approach.

Abstract: Tobacco, alcohol, and drug use are problems for American-Indian people. We reviewed these problems and the explanations for them and described a bicultural competence skills approach for preventing substance abuse with American-Indian adolescents. Data from a study of that approach suggest its efficacy with American-Indian youth. At posttest and a 6-month follow-up, AmericanIndian subjects who received preventive intervention based on bicultural competence skills concepts improved more than did American-Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 23 publications
3
95
0
Order By: Relevance
“…Caetano, Clark, andTam (1998) indicate that colonization has led to the loss of traditional cultural values and norms and has been identified as promoting drug use among American Indians. Regarding acculturation, LaFromboise and Rowe (1983) and Schinke et al (1988) suggested that minority youth may experience an increased amount of pressure in their attempt to fit within both their dominant and minority cultures, and substance use may serve as a coping response to this pressure. Mitchell (1996) stated that this examination entails an investigation of the power relations among different social actors and how they continue to create an atmosphere conducive to the propagation of the problem.…”
Section: American Indian Youth and Substance Usementioning
confidence: 99%
“…Caetano, Clark, andTam (1998) indicate that colonization has led to the loss of traditional cultural values and norms and has been identified as promoting drug use among American Indians. Regarding acculturation, LaFromboise and Rowe (1983) and Schinke et al (1988) suggested that minority youth may experience an increased amount of pressure in their attempt to fit within both their dominant and minority cultures, and substance use may serve as a coping response to this pressure. Mitchell (1996) stated that this examination entails an investigation of the power relations among different social actors and how they continue to create an atmosphere conducive to the propagation of the problem.…”
Section: American Indian Youth and Substance Usementioning
confidence: 99%
“…Although treatment of substance abuse per se is outside the scope of this chapter, we review preventive interventions for substance abuse among American Indian youths because these interventions offer opportunities to look at important issues regarding mental health care for this understudied population. Schinke et al (1988) conducted a bicultural competence skills training intervention for the prevention of substance abuse. In this trial, 137 youths were randomly assigned by reservation site into prevention and control conditions after pretesting.…”
Section: American Indian Substance Abuse Prevention-mentioning
confidence: 99%
“…The percentage of high school and college graduates among Native Americans is lower than among the general population (55% vs. 66%, and 7% vs. 16%, respectively; Schinke et al, 1990). Native Americans have a rate of alcoholism six times greater than that of all other ethnic groups (Schinke et al, 1988).…”
Section: Native Americansmentioning
confidence: 99%